Exploring ASEAN Integration through the Knowledge of Generation Z in Phnom Penh, Cambodia - Chhaihong Kor; Mathul Ka; Vannak Ro; Pio Sario T (MASI Mandiri Edukasi, 2025)
The Association of Southeast Asian Nations (ASEAN) has played a vital role in Cambodia’s economic, political, and social cooperation with its ASEAN member states. Cambodian Generation Z is a dynamic group building a future for Cambodia. This article assesses the level of knowledge about ASEAN integration among Generation Z in Phnom Penh, Cambodia, using a mixed-methods approach with a survey of 414 respondents and 8 key informant interviews. The findings reveal that while Generation Z in Phnom Penh demonstrates some awareness of ASEAN, their overall knowledge remains limited, with notable strengths in cultural awareness and digital engagement but significant gaps in political and economic understanding. Future research should explore factors contributing to knowledge gaps and the impact of digital platforms on awareness. It should also conduct comparative studies across ASEAN countries to understand generational knowledge disparities better.